ACVIM consensus update on Lyme borreliosis in dogs and cats. (22nd March 2018) - Littman, Meryl P.; Gerber, Bernhard; Goldstein, Richard E.; Labato, Mary Anna; Lappin, Michael R.; Moore, George E.
Abstract : An update of the 2006 American College of Veterinary Internal Medicine (ACVIM) Small Animal Consensus Statement on Lyme Disease in Dogs: Diagnosis, Treatment, and Prevention was presented at the 2016 ACVIM Forum in Denver, CO, followed by panel and audience discussion and a drafted consensus statement distributed online to diplomates for comment. The updated consensus statement is presented below. The consensus statement aims to provide guidance on the diagnosis, treatment, and prevention of Lyme borreliosis in dogs and cats.